Audit of Neonatal Morbidity and Mortality in A Tertiary Care Hospital, Sylhet - Hamid, Farzana; Quaium, Syed Moosa MA; Rahman, Azizur; Ahmad, AT Reza; Khan, Shahariar; Hussain, Tania; Zahra, Fatematuz; Islam, Tahi MD Tahmid (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: To know the disease pattern and causes of morbidity & mortality of patients admitted to the neonatal unit in a tertiary care hospital in Sylhet, Bangladesh. Methods: This retrospective study was conducted in the neonatal unit from December 2014 to November 2015. Data of all the patients admitted to the neonatal unit during study period was analyzed for, age, sex, weight, gestational age, place and mode of delivery, maternal antenatal events, disease pattern and their outcome. Results: A total of 985 patients were admitted during study period. Among 985 cases 566(57.5%) were male and 419(42.5%) were female. 450(45.6%) were admitted at the age of less than 24 hours. 122 (12.4%) were preterm babies. 202(20.5%) were low birth weight. 693(70.4%) were delivered in hospital. Main causes of admission were perinatal asphyxia 398(40.4%), neonatal sepsis164 (16.6%), preterm LBW 122(12.4%), Meconium Stained Baby (MSB) 88(8.9%), Intrauterine Growth Retardation (IUGR) 80(8.1%), neonatal jaundice 62(6.2%), Infant of Diabetic Mother (IDM) 30(3.0%), Transient Tachypnoea of Newborn (TTN) 15(1.5%), Meconium Aspiration Syndrome (MAS) 10(1.1%), Respiratory Distress Syndrome (RDS) 6(0.6%) and congenital anomaly 10(1.1%). Most of the deaths were associated with preterm LBW (6.5%), perinatal asphyxia with Hypoxic Ischaemic Encephalopathy (HIE) (4.5%), sepsis (2.4%), RDS (16.7%), MAS (10%). Conclusion: Preterm LBW, perinatal asphyxia and neonatal sepsis were the three leading cause of neonatal morbidity & mortality. These findings could be important in identifying the areas requiring attention to improve the perinatal care and also to manage the problems associated with them. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 45-48